Ram semen deterioration by short-term exposure to high altitude is prevented by improvement of antioxidant status. (9th October 2017) - Cofré, E.; Peralta, O. A.; Raggi, A.; De los Reyes, M.; Sales, F.; González-Bulnes, A.; Parraguez, V. H.
Abstract : Ovine reproduction efficiency in herds at high altitude ( ha ) is lower than that at low altitude ( la ). In ewes, ha effects are due to hypoxia and oxidative stress. Our aim was to establish the effect of antioxidant vitamin supplementation on semen traits and antioxidant status of rams exposed to short or long time ha . A total of 32 rams native to la ( 500 m) were used, 16 were kept at la and the other 16 were brought to ha ( 3600 m), where they were placed in the same flock as the ha native rams ( n =16). Half of the animals in each group were supplemented daily with vitamins C 600 mg and E 450 IU per os, during the entire experimental period, starting the 4th day after animal's arrival at ha (day 0). At days 0, 30 and 60 of treatment, blood and semen samples were collected for evaluation of antioxidant status and semen standard characteristics. Data were compared within each experimental time by analysis of variance using a general linear model. Elevated concentrations of oxidative stress biomarkers were present in blood from animals maintained at ha . Ejaculates from ha exposed rams showed decreased sperm concentration, progressive motility and viability, in addition to decreased antioxidant status in seminal fluid. A total of 30 days of oral supplementation with vitamins C and E prevented some ha negative effects on semen characteristics, mainly in recently ha exposed rams. It is concluded that exposure of rams to ha negatively affects semen quality, where oxidative stress plays a predominant role. These effects are mainly prevented by oral supplementation of vitamins C and E, which constitutes a simple and cheap alternative to improve semen quality of rams when they are moved to ha.